2002
DOI: 10.1038/sj.bjc.6600040
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of dihydropyrimidine dehydrogenase expression in breast cancer

Abstract: We have investigated dihydropyrimidine dehydrogenase expression as a prognostic marker in breast cancer. A total of 119 women with breast cancer undergoing surgery between 1985 and 1996 were included in this study. Eighty-seven patients were treated with postoperative chemotherapy including 5-fluorouracil or 5-fluorouracil derivatives. Fifty-nine (50%) of 119 patients were determined to be immunostaining-positive for dihydropyrimidine dehydrogenase. There was no significant difference between dihydropyrimidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…Half of the breast and gastric cancer tissues lacked DPD expression. A similar immunohistochemical finding was shown in breast cancers by Horiguchi et al [9]. In our study, eight of nine poorly differentiated adenocarcinomas of the stomach were negative for DPD.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Half of the breast and gastric cancer tissues lacked DPD expression. A similar immunohistochemical finding was shown in breast cancers by Horiguchi et al [9]. In our study, eight of nine poorly differentiated adenocarcinomas of the stomach were negative for DPD.…”
Section: Discussionsupporting
confidence: 71%
“…Significant correlation between the immunohistochemical DPD expression and the 5-FU resistance or poor prognosis has been demonstrated in pulmonary, mammary, and oral carcinomas [9,10,15,22]. Nozawa et al reported that DPD expression in gastric carcinoma was comparable between the biopsy samples and resected surgical specimens [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these proteins have been implicated in metastatic spread of breast cancer. Besides mdr-1 expression, we examined dihydropyrimidine dehydrogenase (DPD) since DPD-positive tumors have been found to be prognostic of poor survival [59]. Similarly, expression of COX-2 is predictive of poor survival [60].…”
Section: The Role Of Pkc-α In Breast Cancermentioning
confidence: 99%
“…In contrast, high DPD expression in many tumors is correlated with resistance to 5-FU. [34][35][36] Moreover, DPD expression is often associated with tumor aggressiveness or poor outcome in some cancers. [34][35][36] Takabayashi …”
Section: Discussionmentioning
confidence: 99%